Cognitive Maps Reveal Diverse Perceptions of How Prescribed Fire Affects Forests and Communities - Hamilton, Matthew; Salerno, Jonathan (Frontiers in Forests and Global Change, 2020)
The potential for prescribed fire to address fuel management and forest restoration goals has received considerable attention. However, many wildfire risk mitigation practitioners and researchers consider prescribed fire to be an underutilized tool for forest and fire management. Prescribed fire can affect a broad range of values (e.g., air quality, wildlife habitat, timber, protection of homes) and these effects, which we term valued outcomes, may result from complex dynamics operating within fire-prone social-ecological systems. Increasing the effective use of prescribed fire requires a better understanding of how these dynamics are perceived by stakeholders, whose support is crucial for forest and fire management initiatives that affect diverse groups of people. We evaluated perceptions of the effects of prescribed fire on valued outcomes using data from 111 cognitive maps elicited from stakeholders in the wildfire-prone Eastern Cascades Ecoregion of central Oregon. As representations of relationships among biological, physical, social, political, and other factors that structure individuals’ understanding of a system, cognitive maps are ideal for analyzing perceptions of dynamics in complex social-ecological systems. We found that prescribed fire was perceived to positively affect valued outcomes in individuals’ cognitive maps. However, when we aggregated individuals’ cognitive maps to evaluate perceptions of prescribed fire at varying stakeholder group sizes, we found that perception of desirable effects declined with group size. Additionally, representatives of fire response and non-governmental organizations tended to perceive prescribed fire more favorably, while private citizens and representatives of private businesses emphasized adverse effects. Finally, we measured how the perceptions of the effects of prescribed fire varied across 15 distinct valued outcomes and found that air quality, aesthetic values, and wildlife habitat were perceived to be most negatively affected by prescribed fire, while cultural and historical values, protection of flora, water quality, and firefighter safety were perceived to be most positively affected. Taken together, our results help to explain the challenge of scaling up the use of prescribed fire and highlight the need for policy processes that account for stakeholders’ views of the multiple—and potentially opposing—effects of prescribed fire on different valued outcomes.